All the colors of the dark : a novel - Whitaker, Chris (New York : Crown, 2024)
"1975 is a time of change in America. The Vietnam War is ending. Muhammad Ali is fighting Joe Frazier. And in the small town of Monta Clare, Missouri, girls are disappearing. When the daughter of a wealthy family is targeted, the most unlikely hero emerges--Patch, a local boy, who saves the girl, and, in doing so, leaves heartache in his wake. Patch and those who love him soon discover that the line between triumph and tragedy has never been finer. And that their search for answers will lead them to truths that could mean losing one another. A missing person mystery, a serial killer thriller, a love story, a unique twist on each, Chris Whitaker has written a novel about what lurks in the shadows of obsession and the blinding light of hope."--
The Pirate and the Beekeeper: 1975 -- The Lovers, The Dreamers: 1975 -- The Painter: 1976 -- The Broken Hearts: 1978 -- The Hunt: 1983 -- Fate: 1990 -- The Break: 1995 -- The Prisoner: 1998 -- Myths and Legends: 2001 -- Acknowledgments -- About the Author.
Keywords: Missing persons -- Fiction; Serial murderers -- Fiction; City and town life -- Fiction; Missouri -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Historical fiction; Psychological fiction; Novels